Self-esteem in the puerperium: performance of the beautician (Research, Society and Development, 2022)
Pregnancy is a time when the female body undergoes several changes, mainly due to the deregulation of hormones to prepare the body for the baby's growth. These changes during pregnancy are among the biggest concerns of women, because after childbirth, physical changes can consequently alter the woman's quality of life, generating low self-esteem. The aim of this study is to describe the role of the beautician in raising the self-esteem of women in the postpartum period. This is an integrative literature review: Research was carried out in electronic databases, such as Scientific Electronic Library Online - Scielo, Bireme, Google Scholar, LILACS (Scientific and Technical Literature of Latin America and the Caribbean) and VHL - Virtual Health Library, articles that presented information on the chosen topic, which could be a literary review or field research. The appropriate articles were selected after reading the review and their introduction, and that fit the adopted inclusion criteria, such as articles that presented the theme in question and that were published between the years 2012 and 2022. The studies that compose this review, show that the role of the beautician in improving the self-esteem of women in the postpartum period is relevant, since it is a phase of a woman's life that produces numerous unsightly changes.